TALENT MANAGEMENT AND WORK MOTIVATION TO IMPROVE PERFORMANCE OF EMPLOYEES - Bella Novinda Damarasri; Eeng Ahman (Dinasti Publisher, 2020)
Purpose - To find out (1) An explanation of employee performance, (2) describing Talent Management, (3) an explanation of Work Motivation, (4) the effect of Talent Management and Work Motivation on Employee Performance. Design / Methodology / Approach – This research was conducted on a sample without random, using descriptive and verification approaches with explanatory research methods and data analysis techniques using multiple linear regression. Finding – Talent Management and Work Motivation affect to Employee Performance Originality - The difference is determined in the independent variables, the object and method of the study, the population and research sample, the research period, the measurement instrument and the results of the research, as well as the theoretical sources based on international journals and books and research results.